New Directions in the Study of African American Recolonization - Tomek, Beverly; Hetrick, Matthew J (Southern Dissent, 2017)
This volume closely examines the movement to resettle black Americans in Africa, an effort led by the American Colonization Society during the nineteenth century and a heavily debated part of American history.